PENYELESAIAN KREDIT MACET OLEH PIHAK PERBANKAN DENGAN CARA NOVASI - rusbandi rusbandi (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTThe most important factor to be able to do innovation is the willingness and ability of prospective new borrowers who will take over the obligation of the debtor jammed. Therefore, the obstacles encountered in the banking practice for the implementation of this novation are: Difficult to find new borrowers who are willing to take over the obligations of the debtor standstill; If the new debtor is willing to take over it did not meet the requirements presented by the creditor, in this case the bank. Or if there is no agreement between the two parties regarding the terms of a novation. For the novation is necessary to have the following stages: The existence of the willingness of prospective new borrowers to take over the debt of the debtor standstill; After the decision of the head office, the branch office will be sending a letter to the new debtor regarding the approval of the bank for their novation; Prospective new borrowers were asked to study the terms and conditions that must be met in novation; Created under the loan agreement between the bank hand with new debtor; Bank requested the notary to make a deed of novation,